(3GdeDJeQ GdGbdjei GdGhd ddGJMGO GdOhdi dLeYjGJ heDSSGJ GdecJHGJ (B((3GdEadG(B) (3ai GdefWbI GdYQHjI (B= The First regional IFLA conference in the Arab Region s - (3GdeDJeQ GdGbdjej ddGJMGO GdOhdi dLeYjGJ heDSSGJ GdecJHGJ (B((3GdEadG(B) (3ai GdefWbI GdYQHjs 2013 : (3GdOhMI(B: (3bWQ(B)s; (3GdGJMGO GdYQHi ddecJHGJ hGdeYdheGJ (B((3GYde(B)s ((3bWQ (B:s (3hRGQI GdKbGaI hGdafhf hGdJQGK (B:s, 2013)
(3jJfGhd GdhYGA GYeGd GdeDJeQ GdGbdjei GdGhd ddGJMGO GdOhdi dLeYjGJ heDSSGJ GdecJHGJ (B((3GdEadG(B) (3ai GdefWbI GdYQHjI hehVhYg Yf (B: (3OhQ GdLeYjGJ hGdecJHGJ GdhWfjI ai OYe MQjI GJGMI GdeYdheGJ ai Xd bhGfjf Mbhb GdedcjI GdacQjI GdPi YbO ai GdOhMI (B(10-11 (3jhfjh (B2013 ) s
(3GdLeghQ GdYGes
Keywords: (3GdeYdheGJ (B: (3Ydes -- (3eDJeQGJs; (3GdecJHGJ (B: (3Ydes -- (3eDJeQGJs